Attitude Scale for Assessing Farmers’ Attitude toward Drip Irrigation - Sahil Boora,; Subhash Chander,; Bas Kaur,; Manisha,; Shubham,; Rohit, (Indian Journal of Extension Education, 2024)
Due to the unavailability of an appropriate scale regarding farmers’ attitude toward drip irrigation technology, the need to develop a scale was acknowledged and an attempt was made to construct a Likert's Summated Rating scale.A total of 72 items were collected with the help of literature review and were screened during 2024based on 14-point criteria suggested by Edward (1957). A total of fifty-nine assertions were chosen, and data were collected through Google form which was sent to seventy-four specialists through email and by visiting to the professors and scientists in the university. A set of statements were eliminated and the remaining ones were chosen for item analysis based on the answers provided by the 30 experts and then it wasadministered to 30 farmers of Fatehabad district in Haryana. The scale's reliability was tested using the odd-even method, and the reliability coefficient was 0.806.The content validity was used to assess the scale's validity. In the end, the finalized scalehad 30 items (18 positive and 12 negative).